A plant-expressed conjugate vaccine breaks CD4+ tolerance and induces potent immunity against metastatic Her2+ breast cancer. (2nd June 2016) - Chotprakaikiat, Warayut; Allen, Alex; Bui-Minh, Duc; Harden, Elena; Jobsri, Jantipa; Cavallo, Federica; Gleba, Yuri; Stevenson, Freda K.; Ottensmeier, Christian; Klimyuk, Victor; Savelyeva, Natalia
ABSTRACT: Passive antibody therapy for cancer is an effective but costly treatment modality. Induction of therapeutically potent anticancer antibodies by active vaccination is an attractive alternative but has proven challenging in cancer due to tolerogenic pressure in patients. Here, we used the clinically relevant cancer target Her2, known to be susceptible to targeting by antibody therapy, to demonstrate how potent antibody can be induced by vaccination. A novel 44kD Her2 protein fragment was generated and found to be highly effective at inducing anti-Her2 antibody including trastuzumab-like reactivities. In the tolerant and spontaneous BALB-neuT mouse model of metastatic breast cancer this Her2-targeting vaccine was only effective if the fragment was conjugated to a foreign immunogenic carrier; Fragment C of tetanus toxin. Only the conjugate vaccine induced high affinity anti-Her2 antibody of multiple isotypes and suppressed tumor development. The magnitude of CD4 + T-cell help and breadth of cytokines secreted by the CD4 + T helper (Th) cells induced to the foreign antigen was critical. We used a highly efficient plant-based bio-manufacturing process for protein antigens, magnICON, for vaccine expression, to underpin feasibility of future clinical testing. Hence, our novel Her2-targeting conjugate vaccine combines preclinical efficacy with clinical deliverability, thus setting the scene for therapeutic testing.